Set configuration influences cardiovascular responses to resistance exercise in postmenopausal females in a randomized crossover trial from the CARE project - María Rúa-Alonso; Jessica Rial-Vázquez; Iván Nine; Juan Fariñas; Borja Revuelta-Lera; Manuel A. Giráldez-García; Eliseo Iglesias-Soler (Scientific Reports)
Abstract This study evaluated the acute cardiovascular responses to resistance exercise (RE) sessions with different set configurations in normotensive and hypertensive postmenopausal females. 50 physically active postmenopausal females performed a control (CON) and three RE sessions matched for total volume (144 repetitions), load (12-repetition maximum load), and total rest time (360s) but differing in set configuration: 4 sets of 9 repetitions with 120 s rest (9 S); 6 sets of 6 repetitions with 72 s rest (6 S); and 9 sets of 4 repetitions with 45 s rest (4 S). Heart rate (HR) was recorded during exercise, while HR variability, baroreflex sensitivity, arterial stiffness, and blood pressure were assessed before and after each session. Peak and mean HR values were higher during exercise in 9 S (p ≤ 0.026). All RE protocols induced cardiac parasympathetic withdrawal, reduction in baroreflex sensitivity, and increased post-exercise arterial stiffness compared to CON. However, in 4 S, cardiac parasympathetic withdrawal and baroreflex impairment were attenuated without a significant increase in arterial stiffness. Additionally, a post-exercise hypotensive response was observed only after 9 S in hypertensive participants (p = 0.004). Shorter set configurations attenuate chronotropic response during RE and mitigate impairments in cardiac autonomic and baroreflex control following RE sessions, without affecting arterial stiffness or blood pressure.